The Influence Of Work Experience, Work Skills And Work Discipline On Effectiveness Of Employee Work At Lahat District Court - Ulhaq, Muhammad Dzia; Minha , Amruzi; Fitriya, Fitriya (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
The research aims to determine and analyze the effect of work experience, work skills and work discipline on the effectiveness of the work of employees at the Lahat District Court. The research method used in this study is a quantitative method using questionnaires distributed to respondents. Test the quality of the data by using the validity test, reliability test, normality test. The analysis used is descriptive analysis and inferential analysis using statistical calculations with multiple regression formulas, partial test simultaneous test and the coefficient of determination. Work Experience has a significant effect simultaneously on the effectiveness of employee work at the Lahat District Court Office. Skills have a significant effect simultaneously on the work effectiveness of employees at the Lahat District Court Office. Work discipline has a significant effect simultaneously on the work effectiveness of employees at the Lahat District Court Office. Work Experience, Skills and Work Discipline simultaneously have a significant effect on the work effectiveness of employees at the Lahat District Court Office.